(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Car bumpers can deform to absorb impact energy. For static and modal analysis, a Benz vehicle bumper was used. These analyses used a variety of bumper materials, including glass-mat thermoplastic, aluminium alloy, and mild steel with chromium plating (GMT). The majority of modern cars have bumpers composed of PC/ABS, a material blend of polycarbonate (PC) and Acrylonitrile butadiene styrene (ABS). PETG, ABS, and TPU. The deformation and strains grow as the car’s speed rises from 55 km/hr to 90 km/hr, according to the static study. At a car speed of 75 km/h, the deformation and stress in the automobile bumper were at their highest. It was found through the static analysis that the stress values for PP material were lower.